Учебник немецкого языка - Агаркова Н. А. Наталия Алексеевна; Волявская Б. С. Белла Семеновна; Спивак Л. Н. Любовь Наумовна; Тарановская Н. М. Наталия Михайловна ([Киев], Изд-во Киевского ун-та, 1965)
Исключено из фонда НТБ ТПУ